1995
DOI: 10.3109/08860229509037616
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Sex-Related Differences in Nephrotoxicity of 1,2-Dichloropropane in Rats

Abstract: The contribution of testosterone to the nephrotoxic effects of 1,2-dichloropropane (DCP) was assessed by a series of castration and sex hormone replacement experiments on Wistar rats. The nephrotoxic action of DCP was evaluated by measuring the accumulation of organic anion and release of aspartate aminotransferase into the incubation medium using a renal cortical slice model. Our data show that sex, castration, and testosterone pretreatment are factors that influence the effect of DCP on renal cortical slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…While castration of males is protective, testosteron treatment of females increased their susceptibility toward renal damage. The authors attributed this to different expression of cytochrome P450s, particularly CYP2E1 [32]. The mRNA expression for CYP2D6 was decreased in tumor tissue in a non gender-related manner.…”
Section: Discussionmentioning
confidence: 92%
“…While castration of males is protective, testosteron treatment of females increased their susceptibility toward renal damage. The authors attributed this to different expression of cytochrome P450s, particularly CYP2E1 [32]. The mRNA expression for CYP2D6 was decreased in tumor tissue in a non gender-related manner.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro, renal cortical slices prepared from male Wistar rat kidney were more sensitive to DCP effects than those from females [110]. Further, in a classic sex hormone paradigm study, Odinecs et al [111] confirmed that male rats are more sensitive than females and that testosterone plays a pivotal role in nephrotoxicity.…”
Section: 2-dibromoethane and 12-dibromo-3-chloropropanementioning
confidence: 94%